Relationship between preoperative lymphocyte to monocyte ratio and surgery outcome in type A aortic dissection - Ma, Ming; Zhu, Feng; Fan, Fudong; Pan, Jun; Cao, Hailong; Zhou, Qing; Wang, Dongjin (Frontiers in Surgery, 2023)
Background: Lymphocyte to monocyte ratio (LMR) is associated with the mortality of cardiovascular disease. However, the relationship between preoperative LMR and the prognosis of patients with Stanford type A aortic dissection (TAAD) undergoing surgical treatment remains to be determined. Methods: We enrolled 879 patients with TAAD undergoing surgical treatment between January 2018 and December 2021. Patients were divided into two groups: the Deceased group and the Survived group. The baseline clinical and operative characteristics of the two groups were compared and analyzed. Results: In univariate and multivariate logistic regression analysis, the association between LMR and in-hospital mortality were significant, and LMR (OR=1.598, 95% CI 1.114-2.485, P=0.022) remained significant after adjusting for confounders. Conclusion: Lower LMR may be independently associated with higher in-hospital mortality in TAAD undergoing surgical treatment.